The True King of the Internet: Kittens, Cat Lovers and Cat Language from the Suburbs to the Center of the Web - Thibault, Mattia; Marino, Gabriele (E|C, 2020)
The paper provides an overview of the macro-isotopy “cat”, a totemic figure disputed between the elitist and often-esoteric subculture related to the origins of Internet and the standardized mass culture permeating social networks. Due to its features, “cat” is a cultural unit which is easy to anthropomorphize and iconize, according to a variety of textual practices, including so-called Internet memes (lolcats) and one of the most interesting examples of sign proliferation to date: the creation of a whole new language (lolspeak) based upon systemic misspellings and mistakes.